Cover Feature: Norbornadiene‐Based Photoswitches with Exceptional Combination of Solar Spectrum Match and Long‐Term Energy Storage (Chem. Eur. J. 49/2018). Issue 49 (17th August 2018) - Jevric, Martyn; Petersen, Anne U.; Mansø, Mads; Kumar Singh, Sandeep; Wang, Zhihang; Dreos, Ambra; Sumby, Christopher; Nielsen, Mogens Brøndsted; Börjesson, Karl; Erhart, Paul; Moth‐Poulsen, Kasper
Abstract : Norbornadiene‐quadricyclane (NBD‐QC) photoswitches are candidates for applications in solar thermal energy storage. This work demonstrates that, by modifying the rotational energy landscape of the molecules, it is possible to obtain new solar energy storage systems that exhibit exceptionally long half‐lives for their metastable forms (up to 18 years) without significantly affecting other properties such as solar spectrum match and energy storage density. More information can be found in the Communication by K. Moth‐Poulsen et al. onpage 12767 .